Hell and the Problem of Eternal Evil - Spiegel, James S. (Toronto journal of theology, 2015)
Among the three major views of hell, the traditional view stands alone in affirming eternal conscious torment of the damned. This outcome may or may not be proportionate to the moral crimes human beings commit during their earthly sojourns. But even if there is no justice problem with the view, there remains a serious problem of another sort, for the view implies that evil exists eternally, in the form of unending suffering and moral evil. Just how this moral evil is to be construed depends on the particular form of traditionalism considered. I discuss the two approaches available to the traditionalist—the models of infinite earthly sin and of continuing sin—and show how each account implies the existence of eternal moral evil. The traditionalist, therefore, faces the problem of reconciling belief in God with the fact that a major aspect of reality remains forever unredeemed and in rebellion against God. Failing this, the traditionalist should abandon her view in favour of an alternative perspective to provide a coherent fit with belief in a perfectly good God.